"Children should be seen and not heard": a re-evaluation of certain ancient rules of evidence and procedure that discriminate against the abused child - Berg, Ronel (Institute of Criminology, 2023)
"At the southern tip of the continent of Africa, a rich reward is in the making. This reward will not be measured in money. It will and must be measured by the happiness and welfare of the children, at once the most vulnerable citizens in any society and the greatest of our treasures. The children must, at last, play in the open veld, no longer tortured by the pangs of hunger, or ravaged by disease, or threatened with the scourge of ignorance, molestation and abuse, and no longer required to engage in deeds whose gravity exceeds the demands of their tender years. In front of this distinguished audience, we commit the new South Africa to the relentless pursuit of the purposes defined in the World Declaration on the Survival, Protection and Development of the Child."